Ecouniversidade Pan-Amazônica: cartas ecoculturais e tessituras humano-ecoloógica no Alto Solimões/AM - BRAULE, Gilvânia Plácido (Universidade Federal do Oeste do Pará, 2024)
This Thesis Letter in Education in the Amazon dares to establish as its general objective: to construct a conceptual theory of the Pan-Amazonian Eco-University as a socio-educational and scientific territory based on the culture, environment and society in which the undergraduate graduates (2010-2023) of the Institute of Nature and Culture (INC) of the Federal University of Amazonas (Ufam) live, a campus located in the micro-region of Alto Solimões on the border between Brazil, Peru and Colombia. To this end, we achieve the following specific objectives: i) to create an epistemology focused on the knowledge and daily experiences of biohistorical-cultural beings in their natural and cultural environment of interaction and social integration, ii) to present a theory of education that promotes indigenous well-being and non-indigenous well-being based on reflections on experiential knowledge and knowledge constructed in education in the Amazon region; iii) develop a research method considering the feeling/cosmosentiment, knowledge/cosmovision and living well/well-being of the participants; iv) verify how ethnic and sociocultural diversity is presented in the official documents of the University field of study that are related and the recognition of the indigenous being from international policies to higher education institutions; v) know the personal, ethnic, academic-professional profile of undergraduate graduates, and their perceptions, impressions and perspectives regarding Higher Education and the University; vi) Conceptualize EcoUniversity based on oral, written and visual expressions and their possible indicators of an eco-university institution. This qualitative case study brings in its core a transdisciplinary content (object), with a critical-decolonial basis (Freire, 1969; Walsh, 2015), contextual meta-epistemological (Vargas, 2022), philosophy of complexity (Morin, 2000), philosophy of good living (Acosta, 2016; Krenak, 2000) and the epistemology of ecoculturality (Braule; Brasileiro, 2021) created at the beginning of the doctorate. The RSL (Systematic Literature Review) analyzes studies on University and Sociability/Interculturality/Sustainability and highlights advances and gaps regarding the premises of ecoculturality. The analysis of the PDI (Institutional Development Plan) and PPI (Institutional Pedagogical Plan) shows that the University experienced by the graduates contemplates diversity, indigenous people and those who come from traditional populations. However, the ecocultural premises in the PPCs (Course Pedagogical Projects) are presented with little evidence and do not constitute pillars for university education. The human-ecological weaving method, created in this educational research, guided the empirical study in which the participant, as a collaborator and being in possible transformation, begins to weave his/her ecocultural knowledge and actions together with others, (re)constructing his/her feeling/cosmosentiation as a being of nature. The field study occurred in two phases: 1) application of the survey I questionnaire to the population of 1,321 graduates with 453 respondents, generating an initial sample; 2) application of a survey II questionnaire, conversation circles, semi-structured interviews and workshops called tapiris, huts and ecocultural basketry with a sample group of 28 participants from the respondents, using inclusion/exclusion criteria, with equivalence of course, indigenous and non-indigenous and gender. They perceive their University as a field of multiple beings, knowledge and cultures, however, they emphasize the need for greater listening and appreciation of local knowledge; they also conceptualize Ecouniversity as an Ecocultural University of multiworlds in epistemic, cultural and environmental connections. Thus, the Pan-Amazonian Ecouniversity is conceptualized as a field of Higher Education and Sciences with the mission of cultivating knowledge with epistemic premises and ecocultural practices for “living well” and “good living” among the peoples that constitute it.
Keywords: Ecoculturalidade; Educação ecocultural; Tessitura humano-ecológica; EcoUniversidade; Pan-Amazônia; CNPQ:: CIÊNCIAS HUMANAS; Educação na Amazônia - formação do educador, práxis pedagógica e currículo